ANALISIS DAYA SAING DAN FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI INDONESIA DI PASAR INTERNASIONAL - Utami, Ni Made Astuti Wahyu; Dewi, Ratna Komala (JURNAL MANAJEMEN AGRIBISNIS, 2018)
This study focuses on competitiveness analysis and factors influencing Indonesian coffee exports in the international market. The method used in this research is descriptive and quantitative methods. The data were analyzed using analysis of revealed comparative advantage (RCA) and export product dynamic (EPD) analysis to analyze competitiveness and multiple linear regression was used to find out variables that influenced the export volume of Indonesian coffee. Results from the competitiveness analysis using RCA shows that the Indonesian coffee has a strong competitiveness position with RCA value >1 in six export destination United States, Japan, Germany, Malaysia, Italy and Russia. Result from EPD analysis shows that Indonesian coffee exported to United States, Japanese, Germany, Malaysia, Italy and Russia belong to the "Rising Star" position. In the analysis of factors affecting the export volume of Indonesian coffee in the international market showed that the GDP, real exchange rate, and export prices significantly affected the export volume of Indonesian coffee at the confidence level of five percent. Suggested to the Indonesian government to encourage Indonesian coffee to survive in rising star position and to be able to hold  its competitive position.